KAJIAN PELUANG PENERAPAN PRODUKSI BERSIH DI INDUSTRI TAHU (Studi Kasus pada Beberapa Industri Tahu di Kota Martapura, Sumatera Selatan) - Rani Anggraini; Suprihatin Suprihatin; Natiti Siswi Indrasti (Department of Agroindustrial Technology, Bogor Agricultural University, 2022)
The production process in some tofu industries face some problems, both in the production process, industrial management, and environmental management. This research aimed to find out strategies to improve efficiency in tofu production through materials, water and energy saving and to improve environmental quality through minimization and utilization of waste with cleaner production options. The method used was a cleaner production audit by identify problems until analyzing the feasibility of several aspects. The research was conducted in three tofu factories with a daily production capacity of 80 kg/day (Factory A), 220 kg/day (Factory B), and 500 kg/day (Factory C). Based on the research results, some problems were identified on various aspects and some recommendation alternatives of cleaner production in the three factories are identified covering: washing soybeans gradually, re-filtering the remaining washing and soaking water, using a boiler for cooking with steam system (factory A only), Good Manufacturing Practices (GMP), utilization of solid and liquid waste. If cleaner production is implemented, the total energy consumption per kg of soybeans from the three factories could be decreased to 15.87; 20.69 and 8.63 MJ/kg of soybeans, respectively. The percentage reduction in waste water would range from 24.76-36.08%. Tofu production could be increased by 5.19%, the utilization of firewood could be reduced by 64.42% and the savings obtained would range from 2.2-16.9 million rupiah/month. Based on the results of the quantitative feasibility analysis, the five cleaner production options are feasible and should beapplied in practices.Keywords: alternative recommendation, cleaner production, tofu industry